APPLICATION OF SEAMLESS MOBILITY INDICATOR TO BRT TRANSPORTATION SYSTEM PLANNING: SURABAYA CITY STUDY CASE - Kurniawan Bahar, Teddy
The high rate of private vehicle use in Indonesia's major cities has been a problem that affect many sectors in city planning as a whole. This is mainly caused by public transportation's poor services to provide a seamless travel experience from origin to destination points, which makes it less attractive for people to use. Application of smart transportation concept is on of the innovative way to improve the attractiveness of public transportation with integrataion of various existing modes for more optimal multimodal travel and digitilization of existing service operational systems. Through this application, the development of public transportation is directed to be able to embody seamless mobility for easier and more efficient travel. Surabaya as one of the cities that has implemented the Smart City concept has provided Bus Rapid Transit (BRT) system as a form of implementing smart transportation system. This study aims to determine the achievement of BRT public transportation services in Surabaya City in providing seamless mobility trips for the community. BRT as an alternative mode of public transportation has been present in various urban transportation systems in many major cities. Its flexibility in determining the coverage services and lower procurement and management costs compared to other transportation modes make BRT an alternative mode that is more likely to be developed to provide public transportation services in urban areas. BRT services need to have an integrated concept with other alternative mode services and the application of smart technology in its operations. Based on the results of the literature review, both are quite significant factors in providing more efficient and easier travel. Integration focuses on improving inter-connectivity through optimization of transit points and access points for pedestrians and non-motorized vehicles, as well as improving synchronization and reliability in scheduling mode departures. Smart technology applications are used to develop payment services, ticketing, and information systems that provide more convenience for passengers. From there, five seamless mobility objectives were identified to be achieved, namely the inter-connecting different mode alternatives, optimization of synchronization and reliability of mode schedules, application of one-ticket journey, improvement of safety and comfort levels, and provision of dynamic information systems. The five objectives were used as a reference in formulating the seamless mobility indicators used in the analysis process.iv The analysis process was conducted using a Gap Analysis approach to identify the existing conditions and the desired conditions in the BRT service. Both conditions were identified by observing the existing facility services and comparing them with the seamless standards that need to be achieved as well as collecting user preferences in assessing these. User preferences were analyzed to produce an index level that represents the level of quality of existing service conditions in achieving seamless mobility. Measurement is carried out using the Customer Satisfaction Index (CSI) calculation method and the Importance Performance Analysis (IPA) Matrix to generate prioritization proposals for further development. The analysis was carried out using 24 seamless mobility indicators in assessing the quality of seamlessness of existing services. The results of the analysis show that of the 24 indicators, only 5 seamless mobility indicators are categorized as meeting existing standards. In addition, the level of passenger satisfaction in the provision of seamless mobility in Surabaya City is 52%, which means that it is quite satisfied. This figure is in a threshold condition which, if there is no significant development in the future, will decrease. The IPA Matrix results show that in order to optimize existing services, improvements need to focus on attributes that are considered to have a high level of importance and poor performance quality. The prioritized indicators that need to be developed are Bicycle Paths, Intermodal Access Distance, Departure and Arrival Schedules, Waiting Time, Access Comfort, and Transit Comfort.